Changes in Nursing Ethics Education in Lithuania - Toliušienė, Jolanta (Nursing ethics, 2007)
The post-Soviet scene in Lithuania is one of rapid change in medical and nursing ethics. A short introduction to the current background sets the scene for a wider discussion of ethics in health care professionals' education. Lithuania had to adapt rapidly from a politicized nursing and ethics curriculum to European regulations, and from a paternalistic style of care to one of engagement with choices and dilemmas. The relationships between professionals, and between professionals and patients, are affected by this in particular. This short article highlights these issues and how they impact on all involved.